Wegener's Granulomatosis: A Rare Cause of Hydronephrosis - Julien Lillaz; Stéphane Bernardini; Marie-Paule Algros; Hugues Bittard; François Kleinclauss (Case Reports in Medicine)
A seventy-one-year-old woman was hospitalized at our institution for a right-sided “renal colic” associated with an infectious background. Alithiasic ureterohydronephrosis was diagnosed by imaging. A urinary diversion was thus performed using a double J endoureteral stent. The etiologic assessment of the hydronephrosis showed the presence of a periureteral mass that caused extrinsic ureteral compression. After surgical excision of the ureteral lesion, the Wegener's granulomatosis diagnosis was established. This report is the clinical description of a case of “atypical” Wegener's granulomatosis revealed by the onset of a ureteral disease mimicking a neoplastic process.